A Survey on Association Rule Mining Algorithms for Frequent Itemsets - Senthil Kumar, D; Jayaveeran, N (International Journal of Computer Sciences and Engineering, 2025)
These days many current data mining tasks are accomplished successfully only in discovery of Association rule. It appeals more attention in frequent pattern mining because of its wide applicability. Many researchers successfully presented several efficient algorithms with its performances in the area of rule generation. This paper mainly assembles a theoretical survey of the existing algorithms. Here author provides the considered Association rule mining algorithms by beginning an overview of some of the latest research works done on this area. Finally, discusses and concludes the merits and limitation.